A cross-sectional follow up study to estimate seroprevalence of coronavirus disease 2019 in Kobe, Japan. Issue 48 (3rd December 2021) - Doi, Asako; Iwata, Kentaro; Kuroda, Hirokazu; Hasuike, Toshikazu; Nasu, Seiko; Nishioka, Hiroaki; Tomii, Keisuke; Morimoto, Takeshi; Kihara, Yasuki
Abstract : Abstract: We conducted a study to estimate the seroprevalence of coronavirus disease 2019 (COVID-19) in Kobe, Japan with positive immunoglobulin G (IgG) rate of 3.3% (95% confidence interval [CI] 2.3%–4.6%) in April 2020. Because there were large concerns about the spread of COVID-19 among citizens thereafter, we conduct a follow-up cross-sectional study to estimate the seroprevalence, and we also added a validation study using a different assay. We conducted cross-sectional serologic testing for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antibody using 1000 samples from patients at outpatient settings who visited the clinic from May 26 to June 7, 2020, stratified by the decade of age and sex. We used both Kurabo and Abbott serology assays to identify IgG against SARS-CoV-2. There were 18 and 2 positive IgG among 1000 serum samples using Kurabo and Abbott serology assays, respectively (1.8%, 95% CI 1.1%–2.8%, and 0.2%, 95% CI 0.02%–0.7% respectively). By applying the latter figure to the census of Kobe City (population: 1, 518, 870), it is estimated that the number of people with positive IgG is 3038 (95% CI: 304–10, 632) while a total of 285 patients were identified by polymerase chain reaction (PCR) testing at the end of the study period. Assuming Abbott assay as the reference, Kurabo assay had calculated sensitivity and specificity of 100% and 98.4% respectively. Age and sex adjusted prevalence of positivity was calculated to be 0.17%. We found a lower seroprevalence than 2 months before in Kobe city although the figures were still higher than those detected by PCR. Kurabo assay showed more false positives than true positives despite reasonable sensitivity and specificity, due to low prevalence in Kobe.